A Historical View of Motion Sickness—A Plague at Sea and on Land, Also with Military Impact - Huppert, Doreen; Benson, Judy; Brandt, Thomas (Frontiers in Neurology, 2017)
Seasickness, its triggers, symptoms, and preventive measures were well-known in antiquity. This chapter is based on an analysis of descriptions of motion sickness, in particular seasickness, in ancient Greek, Roman, and Chinese literature. A systematic search was made from the Greek period beginning with Homer in 800 BC to the late Roman period and ending with Aetios Amidenos in 600 AD as well as in the Chinese medical classics dating from around 300 AD. Major aspects are the following: body movements caused by waves were identified in all cultures as the critical stimuli. The ancient Greeks and Romans knew that other illnesses and the mental state could precipitate seasickness and that experienced sailors were highly resistant to it (habituation). The Chinese observed that children were particularly susceptible to motion sickness; they first described the type of motion sickness induced by travelling in carts (cart-sickness) or being transported on a litter or in a sedan chair (litter-sickness). The western classics recommended therapeutic measures like fasting or specific diets, pleasant fragrancies, medicinal plants like white hellebore (containing various alkaloids), or a mixture of wine and wormwood. The East knew more unusual measures, such as drinking the urine of young boys, swallowing white sand-sirup, collecting water drops from a bamboo stick, or hiding earth from the kitchen hearth under the hair. The Greek view of the pathophysiology of seasickness was based on the humoral theory of Empedokles and Aristoteles and differed from the Chinese medicine of correspondences, which attributed malfunctions to certain body substances and the life force Qi. Many sources emphasized the impact of seasickness on military actions and famous naval battles such as the Battle of the Red Cliff, which marked the end of the Han dynasty in China, or the defeat of the Spanish Armada by the English in 1588. A peculiar form of motion sickness is associated with Napoleon’s camel corps during the Egyptian campaign of 1798/1799, a sickness induced by riding on a camel. Thus motion sickness in antiquity was known as a physiological response to unadapted body motions during passive transportation as well as a plague.